Abortion induces reactivation of inflammation in relapsing-remitting multiple sclerosis. Issue 12 (3rd July 2018) - Landi, Doriana; Ragonese, Paolo; Prosperini, Luca; Nociti, Viviana; Haggiag, Shalom; Cortese, Antonio; Fantozzi, Roberta; Pontecorvo, Simona; Ferraro, Elisabetta; Buscarinu, Maria Chiara; Mataluni, Giorgia; Monteleone, Fabrizia; et al.
Abstract : Objective: To investigate clinical and radiological outcomes of women with relapsing-remitting multiple sclerosis (RRMS) undergoing abortion. Methods: An independent, multicentre retrospective study was conducted collecting data from eight Italian MS centres. We compared the preconception and postabortion annualised relapse rate (ARR) and number of Gadolinium enhancing (Gd+) lesions, by analyses of covariance. Variables associated with postabortion clinical and MRI activity were investigated using Poisson regression models; each abortion was considered as a statistical unit. Results: From 1995 to 2017, we observed 188 abortions (17 elective) in 153 women with RRMS. Abortions occurred after a mean time of 9.5 (4.4) weeks from estimated conception date. In 86 events out of 188, conception happened during treatment with disease modifying drugs. The mean postabortion ARR (0.63±0.74) was significantly increased (p=0.037) compared with the preconception year (0.50±0.71) as well as the postabortion mean number of new Gd+ lesions (0.77±1.40 vs 0.39±1.04; p=0.004). Higher likelihood of relapses was predicted by higher preconception ARR, discontinuation of preconception treatment and elective abortion; the occurrence of new Gd+ lesions was associated with higher preconception number of active lesions, discontinuation of preconception treatment, shorter length of pregnancy maintenance and elective abortion. Conclusions: Abortion was associated with clinical and radiological inflammatory rebound remarkably in the first 12 months postevent. Deregulated proinflammatory processes arising at the early stages of pregnancy might play a role both in MS reactivation and abortion. Women with MS should be counselled about these risks of abortion and followed up accordingly.